Optimizing Malignant Pilomatricoma Management: The Role of Wide Excision and Adjuvant Radiation - Saputra, Rudi; Ruslim, Samuel Kelvin; Hariyanto, Agustinus Darmadi; Setyorini, Yulita Pundewi; Pualillin, Elvis Deddy Kurniawan (Indonesian Journal of Cancer, 2025)
Introduction: Malignant pilomatricoma is a type of cancer that is rarely found. There are no standard guidelines for treating this condition. This study aims to evaluate the effectiveness of wide excision combined with adjuvant radiation therapy in optimizing the management of malignant pilomatricoma. Case Presentation: A 50-year-old male presented with a complaint of a growing mass on his head for the past four years. Subsequently, the patient underwent wide excision surgery and flap reconstruction. Based on histopathological examination, the mass was revealed to be a malignant pilomatricoma. Following this, the patient received radiation therapy using External Beam Radiation Therapy (EBRT) at a total dosage of 70 Gy over 35 sessions. The patient did not report any complaints during the 3-year follow-up.Conclusion: The combination of wide excision and adjuvant radiation therapy showed positive results in managing malignant pilomatricoma, with no recurrence or metastasis over three years of follow-up. These results suggest that radiation therapy may play a role in optimizing disease control after surgery. Further research is needed to establish more effective treatment guidelines